Preparation method of electrode for in-situ growth of cerium-based polycarboxylic acid metal organic framework material on surface

CN122992093APending Publication Date: 2026-10-27JIANG SU MEI MIAO CHU NENG KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610902721.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明要解决的技术问题是:提供一种表面原位生长铈基多羧酸金属有机框架材料的电极制备方法,克服现有铈基多羧酸配位材料负载粉末涂覆粘接的结合力弱和界面电阻高等问题,同时,也是克服铈离子(Ce3+/Ce4+)虽然有助于构建三维结构有机-无机杂化薄膜、但目前在原位生长方面还没有较好的工艺对此加以利用的问题

Benefits of technology

[0025]本发明的有益效果是:本发明通过酸处理活化电极表面,再采用水热反应在电极表面原位生长铈基多羧酸MOF,并经煅烧处理,显著提高了MOF与电极基底的结合强度和分布均匀性,简化了制备流程,所得复合材料电极也能应用于电化学传感、超级电容器和电催化等领域,具体体现为:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992093A_ABST
    Figure CN122992093A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of all-vanadium redox flow batteries, and particularly relates to a method for preparing an electrode with cerium-based polycarboxylic acid metal organic framework material grown in situ on the surface, which overcomes the problems of weak binding force and high interface resistance of a cerium-based polycarboxylic acid coordination material loaded powder coating and bonding. The steps are as follows: (1) electrode surface activation: the electrode is placed in concentrated sulfuric acid for acid treatment, then washed with deionized water until neutral, and dried; (2) preparation of a precursor mixed solution: polycarboxylic acid ligand is dissolved in a first solvent, and cerium salt is dissolved in a second solvent, then the two obtained solutions are mixed to prepare a precursor mixed solution, or one of the polycarboxylic acid ligand and the cerium salt is dissolved in a solvent, then the other is added and dissolved again to prepare the precursor mixed solution; (3) the precursor mixed solution is added to a hydrothermal reaction kettle, and the electrode of step (1) is placed in the hydrothermal reaction kettle for hydrothermal reaction; (4) ultrasonic cleaning of the electrode; (5) vacuum drying of the electrode; and (6) calcination of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of vanadium redox flow battery technology, and in particular, it relates to an electrode preparation method for in-situ growth of cerium-based polycarboxylic acid metal-organic framework materials on the surface. Background Technology

[0002] In the field of electrochemical energy storage and sensing, the interfacial properties of electrode materials directly determine the overall performance of the device. Constructing functional coatings with high specific surface area, abundant active sites, and good stability on the surface of conductive substrates is an effective way to improve electrode efficiency. In recent years, surface modification layers formed by coordination between polycarboxylic acid organic ligands and rare earth metal ions (especially cerium) have attracted widespread attention due to their unique redox properties, good thermal stability, and tunable chemical functions. 3+ / Ce 4+ It has a variable valence state and can provide additional Faraday capacitance or catalytic activity in electrochemical reactions, while polycarboxylic acid ligands (such as pyromellitic acid, terephthalic acid, etc.) can form a stable coordination network with cerium ions through multiple carboxyl groups, and construct an organic-inorganic hybrid film with a three-dimensional structure on the electrode surface.

[0003] However, existing technologies typically employ a post-modification process of "first synthesizing powder, then coating and bonding" when loading such cerium-based polycarboxylic acid coordination materials onto electrode surfaces. This process has the following inherent drawbacks: First, the pre-synthesized powder and the electrode substrate only have physical contact, resulting in weak adhesion. Over long-term use or under high current density, the powder is prone to detachment, leading to a decrease in device cycle stability. Second, non-conductive adhesives (such as polyvinylidene fluoride, Nafion, etc.) must be added during the coating process, which significantly increases interfacial resistance and reduces the utilization rate of active sites. Third, the multi-step operation results in poor batch-to-batch repeatability, making it difficult to meet the needs of large-scale preparation.

[0004] To address these challenges, researchers have developed a strategy for "in-situ growth" of functional coatings on electrode surfaces. In-situ growth enables chemical bonding or strong physical anchoring between the coordination material and the conductive substrate, avoiding the use of adhesives. It also facilitates the construction of continuous thin-film structures with fast electron transport channels. Currently, there is considerable research on the in-situ growth of polycarboxylic acid coordination systems for transition metals such as copper, cobalt, nickel, and zinc. However, the direct in-situ growth of cerium-based polycarboxylic acid coordination materials on electrode surfaces still faces unique challenges: cerium ions (especially Ce)... 4+It is highly susceptible to hydrolysis and has complex reaction kinetics, which often results in uneven coatings with low coverage on the electrode surface. Moreover, the concentration and ratio range of the precursor solution is narrow, the process window is narrow, and it is highly sensitive to conditions such as temperature and solvent, resulting in poor reproducibility. In addition, the directly grown cerium-based organic-inorganic hybrid layer often has low conductivity and requires subsequent heat treatment to improve its electrochemical performance. However, improper heat treatment process can damage the bonding between the coating and the substrate.

[0005] Therefore, developing a method for preparing cerium-based polycarboxylic acid coordination materials that can grow uniformly, firmly, and with excellent electrochemical performance in situ on the electrode surface has significant technical value and practical significance. Summary of the Invention

[0006] The technical problem to be solved by this invention is to provide an electrode preparation method for in-situ growth of cerium-based polycarboxylic acid metal-organic framework materials, overcoming the problems of weak bonding and high interfacial resistance in existing cerium-based polycarboxylic acid coordination materials with loaded powder coating, and also overcoming the problems of cerium ion (Ce) bonding. 3+ / Ce 4+ While it helps in the construction of three-dimensional organic-inorganic hybrid thin films, there is currently no good process to take advantage of this in in-situ growth.

[0007] The technical solution adopted by this invention to solve its technical problem is: a method for preparing an electrode by in-situ growth of cerium-based polycarboxylic acid metal-organic framework materials, comprising the following steps:

[0008] (1) Electrode surface activation: The electrode is placed in concentrated sulfuric acid for acid treatment, then rinsed with deionized water until neutral and dried;

[0009] (2) Preparation of precursor mixture: Dissolve the polycarboxylic acid ligand in the first solvent and the cerium salt in the second solvent. Mix the two solutions to prepare the precursor mixture. Alternatively, dissolve one of the polycarboxylic acid ligand and the cerium salt in the solvent and then add the other solvent to dissolve again to prepare the precursor mixture.

[0010] The molar ratio of polycarboxylic acid ligand to cerium in the precursor mixture is 4~16:1, and the total mass content of the polycarboxylic acid ligand and cerium salt in the precursor mixture is 0.5%~5.0%.

[0011] (3) Add the precursor mixture obtained in step (2) into the hydrothermal reactor, and put the electrode obtained in step (1) into the hydrothermal reactor to carry out the hydrothermal reaction;

[0012] (4) After the reaction is complete, the electrodes are ultrasonically cleaned;

[0013] (5) The cleaned electrodes are then vacuum dried;

[0014] (6) Calcine the dried electrode.

[0015] In step (2) above, dissolving the polycarboxylic acid ligand and cerium salt separately is to slow down the coordination reaction rate, avoid the formation of amorphous aggregates or gels, and ensure that MOF (metal-organic frameworks) can grow uniformly and orderly in situ on the electrode surface.

[0016] Specifically, the acid treatment conditions in step (1) are a temperature of 50~120℃ and a time of 0.5~6 hours; the concentrated sulfuric acid is sulfuric acid with a mass fraction of 98%.

[0017] Specifically, in step (2), the polycarboxylic acid ligand is selected from one of pyromellitic acid, terephthalic acid, pyromellitic tetracarboxylic acid, or 2-methylimidazole.

[0018] Specifically, in step (2), the polycarboxylic acid ligand is dissolved in the first solvent, and the cerium salt is dissolved in the second solvent. The two solutions are then mixed to form a precursor mixture. Both the first solvent and the second solvent are polar aprotic solvents and are selected from one of N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone or dimethyl sulfoxide. The first solvent and the second solvent can be the same type of polar aprotic solvent or different types of polar aprotic solvents.

[0019] Specifically, in step (2), one of the polycarboxylic acid ligands and cerium salts is dissolved in a solvent and then the other is added and dissolved again to prepare a precursor mixture; the solvent is a polar aprotic solvent selected from N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone or dimethyl sulfoxide.

[0020] Specifically, in step (2), the cerium salt is selected from one or more of cerium nitrate, cerium ammonium nitrate, cerium acetate, cerium chloride, cerium sulfate, or cerium(IV) salt hydrate.

[0021] Specifically, in step (2), the stirring time when each substance is dissolved in each solvent is 0.5 to 6 hours, and the stirring time when the two solutions are mixed is 0.5 to 6 hours; in step (3), the hydrothermal reaction conditions are a temperature of 80 to 200°C and a time of 3 to 24 hours.

[0022] Specifically, in step (4), ultrasonic cleaning involves cleaning with DMF and anhydrous ethanol three times in sequence, with each ultrasonic cleaning lasting 5 to 120 minutes; in step (5), the vacuum drying conditions are a temperature of 60 to 120°C and a time of 4 to 12 hours.

[0023] Specifically, the calcination conditions in step (6) are as follows: heating to 400-800°C at a heating rate of 1-10°C per minute and holding for 0.5-6 hours; the calcination is carried out in a tube furnace and protected by an inert gas, which is nitrogen or argon.

[0024] Specifically, in step (2), the polycarboxylic acid ligand is pyromellitic acid, the cerium salt is cerium nitrate, and the first solvent and the second solvent are both N,N-dimethylformamide.

[0025] The beneficial effects of this invention are as follows: By activating the electrode surface through acid treatment, followed by in-situ growth of cerium-based polycarboxylic acid MOFs on the electrode surface using hydrothermal reaction, and then calcination treatment, the bonding strength and distribution uniformity between the MOF and the electrode substrate are significantly improved, the preparation process is simplified, and the resulting composite material electrode can also be applied in fields such as electrochemical sensing, supercapacitors, and electrocatalysis, specifically manifested in:

[0026] First, it has a strong bond and requires no adhesive. The electrode surface is activated by acid treatment, and cerium-based polycarboxylic acid metal-organic framework (MOF) material is grown directly on the electrode in situ during the hydrothermal reaction. This results in a strong chemical bond or physical anchoring between the MOF crystal and the electrode substrate, avoiding the problems of increased interfacial resistance, coverage of active sites, and poor long-term stability caused by the use of adhesives in traditional coating methods.

[0027] Second, the material distribution is uniform and the morphology is controllable. By optimizing the molar ratio of polycarboxylic acid ligands to cerium salts and the total solid content of the mixed solution, combined with suitable hydrothermal reaction conditions, this invention can obtain dense, uniform, and well-crystalline MOF films or nanostructures on the electrode surface. Furthermore, the morphology and thickness of the MOF can be controlled by adjusting the reaction parameters.

[0028] 3. Calcination treatment improves performance. Calcination treatment of in-situ grown MOFs under an inert atmosphere can partially carbonize organic ligands or transform them into cerium-based oxide / carbon composite structures, which can significantly improve the conductivity, thermal stability and electrochemical activity of the material, while maintaining the original porous framework and morphological characteristics. It is especially suitable for applications such as electrocatalysis, supercapacitors and electrochemical sensing.

[0029] Fourth, the process is simple and environmentally friendly. This invention adopts a one-step hydrothermal synthesis combined with post-calcination method, which does not require a complicated template or layer-by-layer self-assembly process. It is easy to operate and scale up. The polar aprotic solvent used can be recycled, and the ultrasonic cleaning step effectively removes unreacted substances physically adsorbed on the surface, ensuring the cleanliness of the electrode surface.

[0030] Fifth, it has strong versatility. This method is not only applicable to a variety of electrode substrates, such as glassy carbon electrodes, nickel foam, carbon paper and metal sheets, but also allows for the preparation of a series of cerium-based MOFs and derivative materials by changing different polycarboxylic acid ligands and cerium salts, to meet different application scenarios. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a SEM image of the modified electrode prepared in Example 2 of the present invention;

[0033] Figure 2 These are XRD comparison diagrams of the comparative examples and Examples 1-3 of the present invention;

[0034] Figure 3 This is a comparison diagram of the Raman spectra of the comparative example and Examples 1-3 of the present invention;

[0035] Figure 4 This is a comparison of the XPS spectra of the comparative example and Examples 1-3 of the present invention;

[0036] Figure 5 This is a comparison chart showing the energy efficiency of the electrodes prepared in the comparative examples and Examples 1-3 of this invention when assembled into single cells at different current densities. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] First, the electrodes targeted by this invention include, but are not limited to, commercially available carbon felt, carbon fiber, carbon woven fabric, carbon cloth, carbon paper, and carbon-based products formed from carbon fiber.

[0039] Comparative example: The original carbon felt electrode (original electrode) was used as the basis for comparative analysis.

[0040] Example 1:

[0041] (1) Acid-treated electrode: Immerse the electrode material to be treated in concentrated sulfuric acid with a mass fraction of 98%, heat it at 80°C for 2 hours. After treatment, take out the electrode, rinse it repeatedly with deionized water until the rinsing solution is neutral, and finally dry it in a vacuum oven at 60°C for later use.

[0042] (2) Prepare two precursor solutions:

[0043] (2a) Dissolve pyromellitic acid (H3BTC) in N,N-dimethylformamide (DMF) and stir until completely dissolved to obtain a ligand solution.

[0044] (2b) Dissolve cerium nitrate hexahydrate (Ce(NO3)3·6H2O) in dimethyl sulfoxide and stir until completely dissolved to obtain a cerium salt solution.

[0045] The molar ratio of pyromellitic acid to cerium nitrate is 8:1, and the total solid content (the ratio of the sum of the masses of pyromellitic acid and cerium nitrate to the total mass of the mixed solution) is controlled to be 2.0%.

[0046] (3) Mixing and stirring: The two solutions obtained in steps (2a) and (2b) are mixed in a beaker and stirred with a magnetic stirrer at room temperature for 2 hours to obtain a homogeneous precursor mixture.

[0047] (4) Hydrothermal reaction: The mixed solution obtained in step (3) is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, and the electrode material after acid treatment in step (1) is immersed in the mixed solution. The reactor is sealed and placed in an oven for hydrothermal reaction at 120°C for 12 hours.

[0048] (5) Ultrasonic cleaning: After the reaction is completed, the electrode is naturally cooled to room temperature. The electrode is then removed and ultrasonically cleaned three times each with DMF and anhydrous ethanol. Each ultrasonic cleaning takes 20 minutes and the ultrasonic frequency is 40 kHz.

[0049] (6) Vacuum drying: Place the cleaned electrode in a vacuum drying oven and dry it for 8 hours at 80℃ and -0.09 MPa.

[0050] (7) Calcination: The dried electrode is transferred to a tube furnace and argon gas (flow rate 50 mL / min) is introduced as a protective gas. The temperature is increased from room temperature to 500℃ at a rate of 5℃ / min and held at 500℃ for 2 hours. After the holding period, the electrode is naturally cooled to room temperature to obtain the cerium-modified electrode, which is the electrode of cerium-based polycarboxylic acid metal-organic framework material grown in situ on the surface.

[0051] Example 2:

[0052] (1) Acid-treated electrode: Immerse the electrode in concentrated sulfuric acid with a mass fraction of 98%, heat it at 100°C for 1 hour, take it out and rinse it with deionized water until neutral, and then vacuum dry it at 60°C for later use.

[0053] (2) Prepare two precursor solutions:

[0054] (2a) Dissolve terephthalic acid (H2BDC) in N,N-dimethylacetamide (DMAc) and stir to dissolve to obtain a ligand solution.

[0055] (2b) Add cerium ammonium nitrate ((NH4)2Ce(NO3)6) to (2a) above, stir to dissolve, and obtain precursor mixture.

[0056] The molar ratio of terephthalic acid to ceric ammonium nitrate is 12:1, and the total solid content (the ratio of the sum of the masses of terephthalic acid and ceric ammonium nitrate to the total mass of the mixed solution) after mixing the two solutions is 1.0%.

[0057] (3) Mixing and stirring: Mix the two solutions and stir magnetically at room temperature for 1 hour to obtain a uniform precursor mixture.

[0058] (4) Hydrothermal reaction: Transfer the mixture to a hydrothermal reactor, place the acid-treated electrode in it, seal it, and react at 150°C for 8 hours.

[0059] (5) Ultrasonic cleaning: After the reaction is complete, remove the electrode and clean it with DMAc and anhydrous ethanol three times each, with each ultrasonic cleaning lasting 15 minutes.

[0060] (6) Vacuum drying: Place the electrode in a vacuum drying oven and dry it at 80°C for 6 hours.

[0061] Calcination: The dried electrode is placed in a tube furnace, nitrogen gas is introduced (flow rate 60 mL / min), and the temperature is increased to 600℃ at a heating rate of 3℃ / min. The temperature is held for 3 hours and then cooled naturally to obtain the cerium-modified electrode.

[0062] Example 3:

[0063] (1) Acid-treated electrode: Immerse the electrode in concentrated sulfuric acid with a mass fraction of 98%, heat it at 60°C for 3 hours, wash it with deionized water until neutral, and then dry it.

[0064] (2) Prepare two precursor solutions:

[0065] (2a) Dissolve 2-methylimidazole in dimethyl sulfoxide (DMSO) and stir to dissolve, to obtain a ligand solution.

[0066] (2b) Dissolve cerium acetate (Ce(OAc)3·xH2O) in DMSO and stir to dissolve, to obtain a cerium salt solution.

[0067] The molar ratio of 2-methylimidazole to cerium acetate is 6:1, and the total solid content (the ratio of the sum of the masses of 2-methylimidazole and cerium acetate to the total mass of the mixed solution) after mixing the two solutions is 4.0%.

[0068] (3) Mixing and stirring: Mix the two solutions and stir magnetically at room temperature for 0.5 hours to obtain a uniform precursor mixture.

[0069] (4) Hydrothermal reaction: Transfer the mixture to a hydrothermal reactor and place the acid-treated electrode inside. Seal and react at 100°C for 20 hours.

[0070] (5) Ultrasonic cleaning: After the reaction is complete, remove the electrode and clean it with DMSO and anhydrous ethanol three times each, with each ultrasonic cleaning lasting 30 minutes.

[0071] (6) Vacuum drying: Place the electrode in a vacuum drying oven and dry it at 60°C for 12 hours.

[0072] (7) Calcination: Place the dried electrode into a tube furnace and introduce argon gas (flow rate 50 mL / min). Heat to 700℃ at a heating rate of 8℃ / min, hold for 1 hour, and then cool naturally to obtain the cerium-modified electrode.

[0073] After the electrodes in the above three embodiments were prepared, XRD, Raman, and XPS were performed on each embodiment to detect their crystal structure, defect degree, and elemental analysis, thereby evaluating the physicochemical properties of the electrodes. Simultaneously, they were assembled into a symmetrical vanadium redox flow single-cell test system to further evaluate the performance of the electrode materials in a single cell. The results demonstrate that... Figure 2 XRD and Figure 4 The XPS spectra show that cerium dioxide was successfully doped into the electrode, and Figure 3 The Raman spectra also confirmed that the ID / IG (defect density) was improved compared with the original electrode, which means that more catalytic active sites may be generated. After assembling it into a single cell, the energy efficiency of the cell was significantly improved at different current densities, especially in Example 3, where the energy efficiency was improved by 6.5% at 300 mA cm-2.

[0074] Figure 1 The image shown is an SEM image of Example 2, which shows that the particles attached to the fiber surface are a uniform MOF polycrystalline structure, indicating that a MOF with a regular crystal morphology has been obtained.

[0075] Will Figure 5The energy efficiency comparison of the electrodes prepared in Examples 1-3 after being assembled into single cells at different current densities is shown in Table 1 below in numerical table form.

[0076] Table 1 compares the energy efficiency of the electrodes prepared in the comparative examples and Examples 1-3 of this invention when assembled into single cells at different current densities.

[0077]

[0078] Table 1 illustrates that, compared with the comparative example (original electrode), the performance of the batteries assembled with the modified electrodes of the examples is improved to varying degrees at different current densities. In particular, Example 3 shows a 6.5% improvement in energy efficiency at 300 mA / cm⁻².

[0079] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing an electrode by in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials, characterized in that: The steps are as follows: (1) Electrode surface activation: The electrode is placed in concentrated sulfuric acid for acid treatment, then rinsed with deionized water until neutral and dried; (2) Preparation of precursor mixture: Dissolve the polycarboxylic acid ligand in the first solvent and the cerium salt in the second solvent. Mix the two solutions to prepare the precursor mixture. Alternatively, dissolve one of the polycarboxylic acid ligand and the cerium salt in the solvent and then add the other solvent to dissolve again to prepare the precursor mixture. The molar ratio of polycarboxylic acid ligand to cerium in the precursor mixture is 4~16:1, and the total mass content of the polycarboxylic acid ligand and cerium salt in the precursor mixture is 0.5%~5.0%. (3) Add the precursor mixture obtained in step (2) into the hydrothermal reactor, and put the electrode obtained in step (1) into the hydrothermal reactor to carry out the hydrothermal reaction; (4) After the reaction is complete, the electrodes are ultrasonically cleaned; (5) The cleaned electrodes are then vacuum dried; (6) Calcine the dried electrode.

2. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: The acid treatment conditions in step (1) are a temperature of 50~120℃ and a time of 0.5~6 hours; the concentrated sulfuric acid is sulfuric acid with a mass fraction of 98%.

3. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: In step (2), the polycarboxylic acid ligand is selected from one of pyromellitic acid, terephthalic acid, pyromellitic tetracarboxylic acid, or 2-methylimidazole.

4. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: In step (2), the polycarboxylic acid ligand is dissolved in the first solvent and the cerium salt is dissolved in the second solvent. The two solutions are then mixed to prepare a precursor mixture. Both the first and second solvents are polar aprotic solvents and are selected from one of N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone or dimethyl sulfoxide.

5. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: In step (2), one of the polycarboxylic acid ligands and cerium salts is dissolved in a solvent, and then the other is added and dissolved again to prepare a precursor mixture; the solvent is a polar aprotic solvent selected from N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone or dimethyl sulfoxide.

6. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: In step (2), the cerium salt is selected from one or more of cerium nitrate, cerium ammonium nitrate, cerium acetate, cerium chloride, cerium sulfate, or cerium(IV) salt hydrate.

7. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: In step (2), the stirring time when each substance is dissolved in each solvent is 0.5 to 6 hours, and the stirring time when the two solutions are mixed is 0.5 to 6 hours; in step (3), the hydrothermal reaction conditions are a temperature of 80 to 200°C and a time of 3 to 24 hours.

8. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: In step (4), ultrasonic cleaning is performed by cleaning with DMF and anhydrous ethanol three times in sequence, with each ultrasonic cleaning lasting 5 to 120 minutes; in step (5), the vacuum drying conditions are a temperature of 60 to 120°C and a time of 4 to 12 hours.

9. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: The calcination conditions in step (6) are as follows: heating to 400-800°C at a heating rate of 1-10°C per minute and holding for 0.5-6 hours; the calcination is carried out in a tube furnace and protected by an inert gas, which is nitrogen or argon.

10. The electrode preparation method for in-situ surface growth of cerium-based polycarboxylic acid metal-organic framework materials according to claim 1, characterized in that: In step (2), the polycarboxylic acid ligand is pyromellitic acid, the cerium salt is cerium nitrate, and the first and second solvents are both N,N-dimethylformamide.